An electromyographic study of abdominal muscle activity in children with spastic cerebral palsy - Saviour Adjenti; Graham Louw; Jennifer Jelsma; Marianne Unger (AOSIS, 2017)
Background: Inadequate knowledge in the recruitment patterns of abdominal muscles in individuals with spastic-type cerebral palsy (STCP). Objectives: To determine whether there is any difference between the neuromuscular activity (activation pattern) of the abdominal muscles in children with STCP and those of their typically developing (TD) peers. Method: The NORAXAN® electromyography (EMG) was used to monitor the neuromuscular activity in abdominal muscles of individuals with STCP (n = 63), and the results were compared with the findings from age-matched TD individuals (n = 82). Results: EMG frequencies were recorded during rest and during active states and compared using repeated measures ANOVA. Spearman's rank order correlation was used to explore relationships between age, body mass index and abdominal muscle activity. With the exception of the rectus abdominis (RA) muscle, the pattern of neuromuscular activity in children with STCP differs significantly from that of their TD peers. Three of the muscles - external oblique abdominis (EO), internal oblique abdominis (IO) and RA - in both groups showed significant changes (p < 0.001) in the frequency of EMG activity between the resting and active states. An elevated EMG activity at rest in the EO and IO was recorded in the STCP group, whereas the RA during resting and active stages showed similar results to TD individuals. Conclusion: The findings from this study suggest that the RA could be targeted during rehabilitation regimens; however, the force generated by this muscle may not be sufficient for the maintenance of trunk stability without optimal support from the EO and IO muscles.